HUBUNGAN LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) KARYAWAN BENGKEL GRAVY AUTO - Ernest, Ernes Willyams Tangadang; Nenny Anggraini; Jonny Siagian (Fakultas Ekonomi Universitas Kristen Indonesia, 2024)
Human resources (HR) are an important asset for the company. Therefore, quality human resources are needed by companies, especially in industrials era 4.0 as it is today. Many companies are competing to obtain human resources with good quality in order to compete. However, companies or organizations also play an important role in creating quality and competent human resources so that good organizational management is needed in order to maintain organizational life, both long and short term. In the course of an organization or company various kinds of problems will arise as happened in the Gravy Auto Workshop which faces the problem that employees are not comfortable with the work environment and are less motivated in carrying out their work, employees who are not enthusiastic about carrying out task for which they are responsible. The attitude of these employees reflects that employees still lack motivation in carrying out their work. Because of these problems, researchers are interested in examining what causes employee work discomfort, by assessing Work Motivation and then associating it with the OCB of Gravy Auto Workshop employees based on the background above. The purpose of researcher in conducting this research was to find out and prove whether work environments and work motivation have a relationship with organization citizenship behavior (OCB). These studies use a quantitative approached, namely an approached that using data analyst in form of number or numbers in collecting basic data. Collecting data in these studies use a survey method by distributing questionnaire to Gravy Auto Workshop employees using hierarchical theory on work environment variables. Hierarchical theory by Abraham H Maslow on work motivation variables and Organizational Citizenship Behavior (OCB) theory. Test result use SPSS 26.0 shows that there is a significancy relationships between work environments and work motivations on OCB. When tested partially the relationship proved significant. Because it is feasible means that work environments and work motivations are important factors in increasing OCB. Keywords: Work Environment, OCB, Work Motivation